2022
DOI: 10.1101/2022.12.23.521726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZBTB20 is Essential for Cochlear Maturation and Hearing in Mice

Abstract: The mammalian cochlear epithelium undergoes substantial remodeling and maturation before the onset of hearing. However, very little is known about the transcriptional network governing cochlear late-stage maturation and particularly the differentiation of its lateral non-sensory region. Here we establish ZBTB20 as an essential transcription factor required for cochlear terminal differentiation and maturation and hearing. ZBTB20 is abundantly expressed in the developing and mature cochlear non-sensory epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…Several lines of evidence including our recently published report suggests that root cells may play important roles in the maintenance of endolymph homeostasis and EP (9,12,10,20). Our findings in this study also support this hypothesis and imply that root cell dysfunction may at least partially contribute to a reduced EP upon deficiency of TH or all known TRs during the critical period of cochlear development (4,6,36).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Several lines of evidence including our recently published report suggests that root cells may play important roles in the maintenance of endolymph homeostasis and EP (9,12,10,20). Our findings in this study also support this hypothesis and imply that root cell dysfunction may at least partially contribute to a reduced EP upon deficiency of TH or all known TRs during the critical period of cochlear development (4,6,36).…”
Section: Discussionsupporting
confidence: 87%
“…We and others have previously shown that root cell cytoplasm and their processes are enriched with acetyl-α-tubulin (13,20,28). To better visualize root cells, we then performed immunofluorescence staining for acetyl-α-tubulin.…”
Section: Hypothyroidism Results In the Disruption In The Outer Sulcus...mentioning
confidence: 99%
See 3 more Smart Citations